Two new species of Scotinella Banks, 1911 (Araneae: Phrurolithidae) from Mexico, with a discussion on the female genitalic morphology and intraspecific variation - Chamé-Vázquez, David; Guzmán-García, Carlos Ernesto; Carrizales, Juan Maldonado- (Zootaxa, 2023)
The taxonomy of the spider family Phrurolithidae in western Mexico remains poorly investigated. In this work, based on both sexes, we describe Scotinella garman sp. nov. and S. poncei sp. nov. from Michoacán. Specimens of the two new species were collected using pitfall traps in a pine forest, organic avocado orchard, and tropical deciduous forest. The two species seem to be sister species as they resemble each other in several morphological characteristics. Females of Scotinella poncei sp. nov. display a striking variability in the size and depth of the atrium and copulatory openings. Moreover, we discuss the female genitalia conformation of Scotinella, specifically the homology of the secondary spermathecae, and record the genus Phonotimpus Gertsch & Davis, 1940 in western Mexico for the first time.